TOTAL VARIATION ESTIMATE OF LEGANDRE QUASIPOLYNOMIALS - Taslakhchyan, A. K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
The paper considers Legandre quasipolynomials, the great coefficients of which are equal to one, and total variation estimate of those polynomials is derived.